2019
DOI: 10.1111/crj.13028
|View full text |Cite
|
Sign up to set email alerts
|

The v‐DECAF score can predict 90‐day all‐cause mortality in patients with COPD exacerbation requiring invasive mechanical ventilation

Abstract: Introduction The DECAF score is a simple and effective tool for predicting mortality in patients hospitalized with acute exacerbations of chronic obstructive pulmonary disease (AECOPD); however, the DECAF score has not been validated in AECOPD patients requiring invasive mechanical ventilation (IMV). We devised the ventilator (v)‐DECAF score, in which “anemia” replaces “acidaemia,” for use in AECOPD patients requiring IMV. The objective of this study was to compare the predictive efficacy of the v‐DECAF score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Seventeen studies involving a total of 8329 participants met all of the criteria. 6 9 26–40 Among them, Echevarria et al 26 28 and Shi et al 27 29 each produced two articles from two different studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen studies involving a total of 8329 participants met all of the criteria. 6 9 26–40 Among them, Echevarria et al 26 28 and Shi et al 27 29 each produced two articles from two different studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, 15 reported the prognostic values of DECAF scores for in-hospital mortality 6 9 26 28 29 31–40 and five studies reported 30-day mortality. 27 28 30 31 33 The cut-off threshold for each study was retrospectively determined based on the ROC curve. For in-hospital mortality, the results of five studies were based on a cut-off value of 4, 9 28 35 37 39 four studies were based on a cut-off value of 3, 6 32 36 40 three studies were based on a cut-off value of 2 30 33 38 and the other three studies did not report a cut-off threshold.…”
Section: Resultsmentioning
confidence: 99%
“…As such, several mortality prediction models for mechanically ventilated patients have been suggested [ 4 , 7 , 8 , 9 , 10 , 11 ]. However, there are few models that are focused on predicting hospital mortality, and most models included only patients with pneumonia or chronic obstructive lung disease.…”
Section: Introductionmentioning
confidence: 99%
“…Requirement for IMV was a signi cant predictor of in-hospital mortality of AECOPD. [21,24] In the Brown study, 38.7% of patients required IMV and multivariate analysis showed the requirement for IMV was importantly associated with in-hospital death. [21] Lindenauer PK et al showed that in-hospital mortality was higher in COPD patients who required IMV than in patients with non-invasive ventilation (NIV).…”
Section: Discussionmentioning
confidence: 99%